The effectiveness of interventions that support penicillin allergy assessment and delabeling of adult and pediatric patients by nonallergy specialists: a systematic review and meta-analysis. (April 2023) - Powell, Neil; Stephens, Jennie; Kohl, Declan; Owens, Rhys; Ahmed, Shadia; Musicha, Crispin; Upton, Mathew; Kent, Bridie; Tonkin-Crine, Sarah; Sandoe, Jonathan
Highlights: Penicillin allergy delabeling by nonallergists is safe. Less intensive methods delabeled a smaller proportion of patients. Once patients were assessed as suitable for testing, rates of delabeling were high. A diverse workforce engaged in delabeling incorrect penicillin allergy records. Penicillin allergy delabeling interventions are described. Abstract : Objectives: Penicillin allergy records are often incorrect and may result in harm. We aimed to systematically review the effectiveness and safety of nonallergist health care worker delivery of penicillin allergy delabeling. Methods: We searched EMBASE/MEDLINE/CINAHL (Ovid), PsycInfo, Web of Science, and Cochrane CENTRAL from inception to January 21, 2022 and unpublished studies and gray literature. The proportion of patients allergic to penicillin delabeled and harmed was calculated using random-effects models. Results: Overall, 5019 patients were delabeled. Using allergy history alone, 14% (95% confidence interval [CI], 9-21%) of 4350 assessed patients were delabeled without reported harm. Direct drug provocation testing resulted in delabeling in 27% (95% CI, 18-37%) of 4207 assessed patients. Of the 1373 patients tested, 98% were delabeled (95% CI, 97-99%), and nonserious harm was reported in 1% (95% CI, 0-2%). Using skin testing, followed by drug provocation testing, 41% (95% CI, 24-59%) of 2890 assessed patients were delabeled. Of the 1294 tested patients, 95.0% (95% CI, 90-99%) were delabeled, and the reported harm was low (0%; (95% CI 0-1%). Conclusion: Penicillin allergy delabeling by nonallergists is efficacious and safe. The proportion of assessed patients who can be delabeled increases with the complexity of testing method, but substantial numbers can be delabeled without skin testing.